Interactive kid's rhyme / Ahmad Nadzrin Mohammad Nizam and Muhammad Ridhuan Hashim - Mohammad Nizam, Ahmad Nadzrin; Hashim, Muhammad Ridhuan (2015)
A toy is an object for a child to play with in the early childhood development. Interactive Kid's Rhyme project is about to modified dot matrix display hardware for an interactive kid's rhyme toy application. This project is basically to impress children in designing toys that is attractive. In this day and age, children prefer something simple and interesting. For example, a lighted swords and toy phones that emit a sound when the phone keyboard is pressed. With the use of LCD and LEDs, the toy will be much attractive. Other than that, the price of the toy is not reasonable based on their quality especially if the toy is included with sound. Toys like this can bring in a good income if sold in the market.